Models of Solvent Penetration in Glassy Polymers With an Emphasis on Case II Diffusion. A Comparative Review - Bargmann, Swantje; McBride, Andrew; Steinmann, Paul (Applied Mechanics Reviews, 2011)
The objective of this review is to provide an overview and a classification of the key literature on models of non-Fickian case II type diffusion. Several extensive review articles concerning non-Fickian diffusion exist in the literature; our objective is not to reproduce these worthy contributions. Rather, we focus on a limited number of, seemingly disparate, notable models and attempt to unify them using the language of thermodynamics and continuum mechanics. This attempted unification of selected models arising from various modeling communities serves to elucidate the key strengths and potential weaknesses of the model
UnivIS-Import:2015-03-09:Pub.2011.tech.FT.FT-TM.models
Keywords: Deformation; Diffusion (Physics); Polymers; Equations; Stress